Pengaruh Theory Of Planned Behavior Terhadap Green Purchase Intention Konsumen Pria Pada Produk Green Skin Care - Wijayanti, Dian Sukma; Hartini, Sri (Arthavidya Jurnal Ilmiah Ekonomi, 2019)
Abstract. The Theory Of Planned Behavior (TPB)  holds that a person's behavioral intention depends on three factors, namely attitudes, subjective norms, and perceived behavioral control. This study wants to try to find out the effect of theory of planned behavior to green purchase intention by using a sample of 200 male respondents using skin care users who have never used green skin care before. This study uses the Structural Equation Model (SEM) using Amos software. The results of the study concluded that attitude toward behavior, subjective norm and perceived behavioral control has a significant impact to Green purchase intention.  Keywords : green skin care, environmental concern, environmental knowledge